Investigating The Use of Illocutionary Acts Performed by Jenna Ortega in Some Interviews - Nine Febrie Novitasari; Royatuz Ziama; Firqo Amelia (Unipdu Jombang, 2023)
The purpose of this study is to identify the types and the functions of illocutionary acts performed by Jenna Ortega in several of her interviews. The data sources used in this descriptive qualitative research are several videos of Jenna Ortega's interviews in 2022 on YouTube. This study uses the theory of Searle (1969) to determine the types of illocutionary act and Yule's theory (1996) to determine the functions of the illocutionary act performed. The results of this study indicate that there are three types of illocutionary acts performed by Jenna Ortega in some of her interviews, they are: assertive, commissive, and expressive. In this study, it was found that assertive was the most frequently used type of illocutionary act and conveying information as the most frequently appeared function of illocutionary act in some of Jenna Ortega's interviews in 2022.